DETECTION SYSTEM OF A NEW-GENERATION BIOANALYTICAL DEVICE - E. V. Sysoev; A. K. Potashnikov; Y. V. Obidin; T. N. Goryachkovskaya; V. S. Bazin; V. M. Popik; S. E. Peltek; N. A. Kolchanov (Вавиловский журнал генетики и селекции)
We designed and manufactured a system for detection of antibodies/antigenes in biological fluids. This system records the kinetics of free immunodiffusion of fluorescent nanocomplexes inside the channels of a microfluid module of a new-generation bioanalytical device. The system consists of four parallel excitation channels, a system for fluorescence detection, and an image-processing program. Antibody/antigen concentrations below 0,1 μg/ml can be detected in biological fluids.